Decontamination of chilli flakes in a fluidized bed using combined technologies: Infrared, UV and ozone. (January 2020) - Watson, Ian; Kamble, Prashant; Shanks, Callum; Khan, Zakir; El Darra, Nada
Abstract: An initial study of the combination of IR, UV and ozone on treating raw and artificially inoculated chilli flakes (CF, Capsicum annum L) was assessed using a specially designed fluidised bed system, in a fused quartz tube, using a distributor plate and filtered air, to keep the CF in an air suspension. The untreated samples, as bought, were contaminated with 1 × 10 6 cfu/g, they were subsequently autoclaved, and inoculated with Escherichia coli (MG1655). The individual treatments were all effective in reducing the bioburden with log reduction and treatment times 6 logs (cfu/g) in ≤20 min for ozone (300 mgO3 hr −>1 ); 7 logs (cfu/g) in ≤40 min, for UV (4 W); and 7 logs (cfu/g) in ≤20 min, for IR (100 W); for stationary air with ozone, and an airflow of 108 Lmin −>1 with UV and IR treatment. The IR was modulated so that the external tube temperature was 58–60 °C. The treatment order was more effective for the IR and UV followed by ozone, than ozone followed by UV and IR (ozone, 10 min, UV and IR 10 min combined), this was due to the higher intial reduction of the UV and IR (0.80 log (cfu/g)) than with ozone first (0.13 log (cfu/g)). Such decontamination systems could be used efficiently when conveying the spices, just prior to aseptic packaging. Highlights: A new method of using a fluidised bed with combined decontamination systems was designed, fabricated and tested Fluidisation theory was less accurate at predicting fluidisation behaviour of chilli flakes than black pepper Ozone (6 logs (cfu/g) in ≤ 20mins), UV (7, ≤ 40) and IR (7; ≤ 20) were effective at decontamination UV and IR (0.80 log (cfu/g)) then ozone gave greater decontamination than ozone (<0.13 log (cfu/g)) then UV and IR